2011
DOI: 10.1111/j.1600-0714.2011.01020.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour infiltrating CD25+ FoxP3+ regulatory T cells (Tregs) relate to tumour grade and stromal inflammation in oral squamous cell carcinoma

Abstract: This research is aimed to quantitate and characterize the subtypes of tumour infiltrating lymphocytes (TILs), in particular the presence of FoxP3+ Tregs in different grades of oral squamous cell carcinoma using monospecific antibody staining of formalin-fixed, paraffin-embedded tissue sections. The correlation between tumour grade and the intensity of tumour infiltrating lymphocytes was tried to be tested, to assume a putative linkage between them. Thirty-four cases of histologically proven primary oral squamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 37 publications
(37 reference statements)
1
34
2
Order By: Relevance
“…Four independent studies have studied the immunolocalized Treg cells in HNSCC and they all highlighted a marked presence of cells in the tumor microenvironment. 20,37,39,42 Two studies prevalently found Tregs at the tumor margins, 39,42 thus sustaining the hypothesis that these cells might oversee the interactions between SCC cells and effector immune cells at the border between tumor and normal tissue.…”
Section: Mechanism Of Treg Accumulation In Hnsccmentioning
confidence: 79%
See 2 more Smart Citations
“…Four independent studies have studied the immunolocalized Treg cells in HNSCC and they all highlighted a marked presence of cells in the tumor microenvironment. 20,37,39,42 Two studies prevalently found Tregs at the tumor margins, 39,42 thus sustaining the hypothesis that these cells might oversee the interactions between SCC cells and effector immune cells at the border between tumor and normal tissue.…”
Section: Mechanism Of Treg Accumulation In Hnsccmentioning
confidence: 79%
“…Several data strongly sustained a negative prognostic index associated to high levels of Tregs, 10,39,41 but other studies described a completely different situation, with high numbers of Treg associated to an improved loco-regional control and better overall survival. 12,42,45,46 These apparent contradictions might be explained, in part by the difficulties to proper identify Treg cells and in part by the tissue dependent modulation of Treg levels; indeed, tumors arising in the rich lymphoid tissue oropharynx have higher level of infiltrating Treg than cancer types arising in larynx.…”
Section: Treg Significance In Hnscc Prognosismentioning
confidence: 98%
See 1 more Smart Citation
“…13,15 Therefore, research into the cellular and molecular features of the immune response to tumors has intensified in recent years in an attempt to obtain a better understanding of the process of tumor progression, to identify more reliable prognostic factors, and to eventually define potential targets for immunotherapeutic strategies. 6,13,22,23 Within the context of immune responses to tumors, studies have highlighted the participation of Treg cells, which can suppress the functions of different immune system cells. 5,9 In this respect, an increase in the number of Treg cells in the tumor microenvironment has been associated with a poorer prognosis of head and neck carcinomas, including SCC of the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors represented a higher proportion in the group of early-stage LLSCCs (data not shown). Although they used the World Health Organization grading system, Al-Qahtani et al 22 also found a positive correlation between the intensity of inflammatory infiltration and the number of Treg cells in the microenvironment of SCCs of the oral cavity.…”
Section: 15mentioning
confidence: 99%